1991
DOI: 10.1039/c39910000095
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of homochiral amino alcohols, aziridines and diamines via homochiral cyclic sulphites

Abstract: Vicinal diols react with thionyl chloride to give 1,2-cyclic sulphites in quantitative yield, which undergo facile ring opening by lithium azide in dimethylformamide to yield azido alcohols and the latter in turn have been stereoselectively transformed into amino alcohols, aziridines and diamines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…31,33,37,44 4.6. General procedure for the synthesis of cyclic sulfites 3 SOCl 2 (3.90 mL, 50 mmol) was added dropwise at 0°C to a solution of tartrate (43 mmol) 1 in CH 2 Cl 2 (20 mL), followed by addition of a catalytic amount of DMF (10 drops).…”
Section: Cyclic Sulfitesmentioning
confidence: 99%
See 1 more Smart Citation
“…31,33,37,44 4.6. General procedure for the synthesis of cyclic sulfites 3 SOCl 2 (3.90 mL, 50 mmol) was added dropwise at 0°C to a solution of tartrate (43 mmol) 1 in CH 2 Cl 2 (20 mL), followed by addition of a catalytic amount of DMF (10 drops).…”
Section: Cyclic Sulfitesmentioning
confidence: 99%
“…Other possibilities for obtaining the azido alcohols 6 are nucleophilic ring openings of the appropriate cyclic sulfites 3, [31][32][33][34][35] sulfates 4, 37 carbonates, 35 and thionocarbonates 5 36,38,39 with NaN 3 . In references describing these reactions, epimerization of the azido alcohols is not mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] Their reactivity is the result of their ring strain which may be due to angle strain, the partial double bond character between the ring oxygen and sulfur atom due to 2p(O)-3d(S) orbital interaction, and the 1,3 non-bonding interactions between the ring oxygen and the exocyclic oxygen atoms. The X-ray analysis of parent ethylene sulfate indicated that this molecule exists in a puckered conformation, with an angle 20.6°b etween the C4 and C5 bond and a O-S-O bond angle of 98.4°w hich is substantially smaller than the strained tetrahedral angle of 109.5°.…”
Section: Resultsmentioning
confidence: 99%
“…These are converted into cyclic sulfates 68 , 95 -97 or cyclic sulfi tes 69 . 98 These compounds are also cleaved by reaction with lithium azide or sodium azide to azidoalcohols which can then be converted into aziridines as above. The sulfates 68 can be prepared in one pot and in high yield from the diols by reaction with thionyl chloride followed by oxidation with sodium periodate and ruthenium trichloride.…”
Section: Aziridines From Epoxides or 12 -Diolsmentioning
confidence: 99%